Influence of pyrolysis temperature on tea waste-based biochar property and function as a heavy metal sorbent in aqueous solution. Issue 1 (1st April 2022) - Cui, X. L.; Zhong, J.; Li, H.X.; Jin, R.Z.; Liu, Y.; Che, X.K.; Yuan, X. T.; Zhang, Q.D.; Fu, H.
Abstract: The properties of biochars and their adsorption performance are highly dependent on the pyrolysis temperature. In this study, tea waste-based biochars at the different pyrolysis temperature (573K-973K) were investigated, and adsorption capacities of heavy metals from solution by biochars were studied. TG/DTA and SEM results showed that with the increased of pyrolysis temperature, the yield of biochar sharply declined and reached stable at 973K. Moreover, low ratios of H/C, O/C and (O+N)/C were obtained at high pyrolysis temperature, which could produce more pore structure and be conducive to the adsorption of heavy metal ions. The adsorption experiments confirmed that the Pb and Zn absorption efficiency at 973K could reach 99.98% and 30.49%, respectively, which was the optimum temperature.